Does structured informational care reduce anxiety in patients undergoing MRI? A quasi-experimental study - Rasheed, Binish; Rahim, Anila; Ghulam Murtaza; Quddusi, Habiba; Ramzan, Zoobia (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the anxiety level in patients undergoing magnetic resonance imaging, and to see if structured informational care reduces anxiety compared to conventional approach. Method: The quasi-experimental study was conducted Dow Institute of Radiology, Dow University of Health Sciences Karachi, Pakistan from January 2020 to June 2021, and comprised adult patients of either gender undergoing magnetic resonance imaging of brain / cervical spine for the first time. They were divided into S-arm group exposed to structured information with pictures, recordings and videos, and C-arm group exposed to conventional information. The primary outcome was anxiety, measured by Beck Anxiety Inventory. Data was analysed using SPSS 11. Results: Of the 280 subjects, 140(50%) were in the S-arm; 65(46.4%) males and 75(53.6%) females with mean age 41.1±15.2 years. The C-arm had 140(50%) subjects; 78(55.7%) males and 62(44.3%) females with mean age 44.2±13.9 years (p>0.05). The pre-procedure anxiety score of C-arm was 11.3±7.7 compared to 9.6±7.7 in S-arm (p=0.062. Post-procedure anxiety score in S-arm was 9.8±9.0 compared to 1.49±4.5 in C-armB (p<0.001). Conclusion: Structured informational care aimed at familiarising the patient to the magnetic resonance imagaing machine and describing the relaxing manoeuvres during examinationI was found to be a cost-effective and simple method to alleviate anxiety in patients. Key Words: Claustrophobia, Premature termination, Magnetic resonance imaging, Anxiety, Structured informational care.